Associação entre trauma na infância e transtorno do humor na vida adulta - Figueiredo, Ângela Leggerini de (2012)
This study is divided into three sections: one theoretical and two empirical studies. The theoretical chapter presents a systematic review were searched the last ten years researches that related Childhood Trauma with mood disorders in adults in empirical studies (cohort or cross). In this review there was a lack of empirical studies that describe these phenomena and their association in our country, from such a reality was outlined to verify the empirical studies of childhood trauma and its association with mood disorders in a clinical population in the city of Porto Alegre. Chapter two describes the frequency of childhood trauma and specified by the most frequent types with the Childhood Trauma Questionnaire. In the third chapter there was an association between trauma in childhood mood disorders, diagnosed from the SCID-I-CV and symptoms of depressive mood (BDI-II) and hypomanic (HCL-32). RESULTS: The frequency of trauma found this population was 44.22%. And that was associated with bipolar disorder and dysthymia. There was also a lack of studies describing and associating factors for the development of psychopathology in the Brazilian reality. Finally difficulty parameters have been firm to carry out intervention strategies and effective prevention.